PENGARUH SISTEM PENGENDALIAN INTERNAL, AKUNTABILITAS, TRANSPARANSI, DAN MORALITAS TERHADAP KECURANGAN DANA BOS PADA SMA KABUPATEN PEMALANG - Andayani, Tutut Dwi; Purnama Sari, Linda; Moegiri, Moegiri; r, Riswan (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2023)
This research aims to investigate the effect of Internal Control System Accountability, Transparency, and Morality on Boss Fund Fraud in schools. This research was conducted at SMA Pemalang Regency. The total population taken is the principal, treasurer boss, and school committees in SMA in Pemalang Regency, totaling 54 people. Data collection is done by distributing questionnaires. The analytical technique used in this study is multiple linear regression using the SPSS (Statistical Product and Service Solutions) version 16 program. The results of this study indicate that; (1)the internal control system has a significant effect on the boss's fund fraud; (2) accountability has no significant effect on the boss's fund fraud; (3) transparency has no significant effect on the boss's fund fraud;(4)morality has a significant effect on the boss's fund fraud; (5) internal control system, accountability, transparency, and morality have a significant effect on the boss's fund fraud.